No place on the corner : the costs of aggressive policing - Haldipur, Jan (New York University Press, 2018)
What's it like to be stopped and frisked by the police while walking home from the supermarket with your young children? How does it feel to receive a phone call from your fourteen-year-old son who is in the back of a squad car because he laughed at a police officer? How does a young person of color cope with being frisked several times a week since the age of 15? These are just some of the stories in No Place on the Corner, which draws on three years of intensive ethnographic fieldwork in the South Bronx before and after the landmark 2013 Floyd v. City of New York decision that ruled that the NYPD's controversial "stop and frisk" policing methods were a violation of rights. Through riveting interviews and with a humane eye, Jan Haldipur shows how a community endured this aggressive policing regime. Though the police mostly targeted younger men of color, Haldipur focuses on how everyone in the neighborhood--mothers, fathers, grandparents, brothers and sisters, even the district attorney's office--was affected by this intense policing regime and thus shows how this South Bronx community as a whole experienced this collective form of punishment. One of Haldipur's key insights is to demonstrate how police patrols effectively cleared the streets of residents and made public spaces feel off-limits or inaccessible to the people who lived there. In this way community members lost the very 'street corner' culture that has been a hallmark of urban spaces. This profound social consequence of aggressive policing effectively keeps neighbors out of one another's lives and deeply hurts a community's sense of cohesion. -- Provided by publisher